Caching personalised and database-related dynamic web pages. (3rd January 2011) - Chang, Yeim-Kuan; Ting, I-Wei; Lin, Yu-Ren
In recent years, web development is the most important application in internet. Caching related technique improves the web server performance significantly. However, existing caching schemes cannot deal with the dynamic web pages efficiently. Thus, in this paper, we propose a caching scheme and then use web session objects and database-related dynamic web cache to implement the dynamic web cache system in Tomcat web server. We show how to build the dependency between dynamic web pages and the underlying database fields and session objects. Our experimental results show that Tomcat with proposed dynamic web cache can increase the stability of web server and improve web server throughput by up to 290%.